PERLINDUNGAN HUKUM MEREK SAH TERHADAP TINDAKAN PEMBONCENGAN REPUTASI (PASSING OFF) - Muhammad Faisal Aditya; Yudho Taruno Muryanto (Fakultas Hukum Universitas Sebelas Maret, 2024)
AbstractThis article examines the form of legal protection for registered trademark rights holders against the existence of a passing off action along with what legal remedies can be taken by the aggrieved parties for the existence of this passing off act. So that through mechanisms both in litigation and non-litigation, it is hoped that it can provide justice for the aggrieved parties. This research is a normative-juridical research which is prescriptive in nature. Types of secondary data include primary, secondary and tertiary legal materials. The data collection technique used is through literature study, research instruments in the form of Undang-Undang No. 20 of 2016 concerning Trademarks and Geographical Indications. The results of this study indicate how the form of legal protection provided by the government for registered trademark rights owners against the act of passing off. The form of protection provided is in the form of granting exclusive rights to use a registered mark in the trade in goods / services, as a